PENGUATAN UMKM MELALUI PENINGKATAN LITERASI HUKUM TERHADAP ERLINDUNGAN HAK MEREK DI DESA PAMANUK KABUPATEN SERANG - Uli Wildan Nuryanto; Mohammad Hifni; Desty Endrawati Subroto; Rizky Dwi Prayoga; Sifa Faujiah; Sherly Paulina; Kamsin Kamsin; Syihabudin Syihabudin (Gapenas Publisher, 2023)
The potential of MSMEs in Pamanuk Village, Carenang District, Serang Regency has the potential to improve the welfare of the surrounding community. However, unfortunately there are still many limitations possessed by MSME players, especially those operating in the micro sector, which means that the competitiveness of these MSMEs is weak. One of the results of observations and empirical studies in the field was that one of the weaknesses came from weak knowledge related to legal literacy and halal certification. For this reason, this research was carried out with the aim of providing understanding to MSME players regarding the legal entity status that MSMEs can have also how to obtain halal certification for those operating in the food and beverage sector. The method used is counseling and training for community groups as MSME actors who will later provide education to other communities about the procedures for obtaining legal entity status and brand right protection. The results of the research show that there have been significant changes in the benefits of managing legal entities in the MSME sector and in increasing the knowledge of MSME actors in Pamanuk Village